2014
DOI: 10.1038/nature13265
|View full text |Cite
|
Sign up to set email alerts
|

Widespread decline of Congo rainforest greenness in the past decade

Abstract: Tropical forests are global epicentres of biodiversity and important modulators of climate change, and are mainly constrained by rainfall patterns. The severe short-term droughts that occurred recently in Amazonia have drawn attention to the vulnerability of tropical forests to climatic disturbances. The central African rainforests, the second-largest on Earth, have experienced a long-term drying trend whose impacts on vegetation dynamics remain mostly unknown because in situ observations are very limited. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
284
3
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 378 publications
(322 citation statements)
references
References 46 publications
17
284
3
2
Order By: Relevance
“…A long-term drying trend was also observed over the northern part of the tropics by Kawase et al (2010), which was mainly caused by an increase in anthropogenic aerosols influencing both atmospheric dynamics and thermodynamic effects. A recent study by Zhou et al (2014) also confirmed a decline in rainfall across the large area of central and northern Democratic Republic of Congo. A reduction in rainfall across tropical ecosystems could have a significant impact on the climatic condition at the global and regional scale considering that the Congo Basin is the second largest rainforest on earth.…”
Section: Rainfall Patternsmentioning
confidence: 74%
See 2 more Smart Citations
“…A long-term drying trend was also observed over the northern part of the tropics by Kawase et al (2010), which was mainly caused by an increase in anthropogenic aerosols influencing both atmospheric dynamics and thermodynamic effects. A recent study by Zhou et al (2014) also confirmed a decline in rainfall across the large area of central and northern Democratic Republic of Congo. A reduction in rainfall across tropical ecosystems could have a significant impact on the climatic condition at the global and regional scale considering that the Congo Basin is the second largest rainforest on earth.…”
Section: Rainfall Patternsmentioning
confidence: 74%
“…The condition of evergreen vegetation across this area remained mainly constant or showed a small but statistically significant increase in NDVI values by <0.005 and <0.01 in contrast to negative rainfall trends of <−30 mm over 10 years. This discrepancy in vegetation patterns may be explained by the fact that Zhou et al (2014) used the Enhanced Vegetation Index (EVI) in their study, which is more sensitive to dense forest than other vegetation indices such as the NDVI used here. EVI has been used widely in recent studies of tropical rainforest in the Amazon (Samanta et al, 2012).…”
Section: A Conceptual Model -Link With Previous Studiesmentioning
confidence: 88%
See 1 more Smart Citation
“…However, they face two threats: changes in land-use, particularly drainage for agricultural use, as is occurring extensively across tropical Asia; and a regional reduction in precipitation via a changing climate, which may already be occurring 32 . While modelled projections of Central African rainfall are not consistent, some suggest declining annual precipitation 7 and more intense dry seasons 8 …”
Section: Main Textmentioning
confidence: 99%
“…T he impacts of climate change and anthropogenic activities on Earth's vegetation and ecosystems have been in the spotlight of science in the past decades [1][2][3][4][5][6] . With increasing climate variability and more frequent occurrences of extreme events expected in the future 7 , research has targeted the sensitivity of ecosystems 8,9 .…”
mentioning
confidence: 99%